Effect of ginger (Zingiber officinale) supplementation on oxidative stress parameters: A systematic review and meta‐analysis. Issue 2 (17th January 2021) - Morvaridzadeh, Mojgan; Sadeghi, Ehsan; Agah, Shahram; Fazelian, Siavash; Rahimlou, Mehran; Kern, Ferdinand Georg; Heshmati, Shilan; Omidi, Amirhosein; Persad, Emma; Heshmati, Javad
Abstract: A wide variety of antioxidant properties are attributed to ginger ( Zingiber officinale ) and several randomized controlled trials (RCTs) have investigated the effect of ginger intake on major oxidative stress (OS) parameters. We conducted a systematic review and meta‐analysis to evaluate the effects of using ginger to improve OS levels. Medline, Scopus, ISI Web of Science, EMBASE, and the Cochrane Central Register of Controlled Trials were systematically searched up until March 2020 to gather RCTs that evaluated the impact of ginger intake on the levels and activity of OS parameters in adult subjects. Means and standard deviations for relevant OS variables were extracted and evaluated to assess the quality of the trials based on the Cochrane risk‐of‐bias tool for randomized trials. The gathered data were pooled and expressed as standardized mean difference (SMD) with 95% Confidence Intervals (95% CI). Twelve trials were included in this review. Ginger intake was shown to significantly increase glutathione peroxidase (GPx) activity (SMD: 1.64; 95% CI: 0.43, 2.85; I 2  = 86.8%) and total antioxidant capacity (TAC) (SMD: 0.40; 95% CI: 0.06, 0.73; I 2  = 42.8%) and significantly decrease malondialdehyde (MDA) levels (SMD: −0.69; 95% CI: −1.26, −0.12; I 2  = 85.8%) compared to control groups. Ginger supplementation also non‐significantly associated with an increase in CAT activity (SMD: 1.09; 95% CI: −0.07, 2.25; I 2  = 87.6%). This systematic review and meta‐analysis presents convincing evidence supporting the efficacy of ginger supplementation on improving OS levels. Practical implications: In health sciences, OS, due to its pivotal role in the pathophysiology of several chronic diseases, is a subject with a long history. Recent research strives for a safe, ideal, and effective antioxidant. Ginger is herbal medicine, which has been widely used in traditional and complementary medicine. Proving the antioxidant effect and potential benefit of ginger has positive clinical implications for the application of this practical herb. Abstract : This systematic review and meta‐analysis present convincing evidence supporting the efficacy of ginger supplementation on improving oxidative stress parameters. Ginger intake was shown to significantly increase glutathione peroxidase (GPx) activity and total antioxidant capacity (TAC) and also significantly decrease malondialdehyde (MDA) levels.